Impact of limited irrigation on the growth characteristics of Lotus corniculatus - Karatassiou M.; Kostopoulou P.; Lazaridou M.; Merou T.; Giagourta P.; Noitsakis B. (Forage resources and ecosystem services provided by Mountain and Mediterranean grasslands and rangelands, 2014)
Drought is the most important environmental stress for plants. Inadequate amount of rainfall or irrigation can reduce plant growth and forage production more than all the other environmental stresses combined. In this experiment the influence of water stress on the growth parameters of Lotus corniculatus was investigated. Plants from a natural population of a semi-arid area of Northern Greece (Drama) were selected and transplanted to pots. After a period of plant establishment, two irrigation regimes were used: (a) irrigation up to field capacity and (b) partial irrigation in order to maintain water shortage conditions in the soil. All measurements were taken during the growing season at four different phenological stages. Total shoot weight, stem weight (SW), leaf weight (LW) and leaf area (LA) were measured during the growing season. Also, the specific leaf area (SLA), leaf area ratio (LAR) and leaf weight ratio (LWR) were calculated. The results showed that the limited irrigation significantly reduced the growth parameters LA, dry SW and LW, while it did not affect the allometric parameters SLA, LAR, and LWR of L. corniculatus.
Joint Meeting of the "Mountain Pastures, Mediterranean Forage Resources (FAO/ESCORENA-CIHEAM) and Mountain Cheese" Network, 2014/06/24-26, Clermont-Ferrand (France)